2009
DOI: 10.1097/gim.0b013e31819d0996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after long-term treatment with alglucosidase alfa in infants and children with advanced Pompe disease

Abstract: Purpose: A clinical trial was conducted to evaluate the safety and efficacy of alglucosidase alfa in infants and children with advanced Pompe disease. Methods: Open-label, multicenter study of IV alglucosidase alfa treatment in 21 infants 3-43 months old (median 13 months) with minimal acid ␣-glucosidase activity and abnormal left ventricular mass index by echocardiography. Patients received IV alglucosidase alfa every 2 weeks for up to 168 weeks (median 120 weeks). Survival results were compared with an untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
209
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(231 citation statements)
references
References 23 publications
(39 reference statements)
7
209
1
3
Order By: Relevance
“…The best skeletal muscle response occurs when ERT is administered prior to skeletal muscle damage. [6,7] Treatment with alglucosidase alfa in late-onset PD is associated with improved walking distance and stabilisation of pulmonary function. [8] Alglucosidase alfa is available in 50 mg dried powder vials.…”
Section: Managementmentioning
confidence: 99%
“…The best skeletal muscle response occurs when ERT is administered prior to skeletal muscle damage. [6,7] Treatment with alglucosidase alfa in late-onset PD is associated with improved walking distance and stabilisation of pulmonary function. [8] Alglucosidase alfa is available in 50 mg dried powder vials.…”
Section: Managementmentioning
confidence: 99%
“…1,4,5 Any delay in diagnosis is not acceptable since it is now well established that an early diagnosis and timely initiation of ERT will have a drastic impact on the natural disease course. 12 The delayed start of ERT, even by only a few weeks increases the morbidity in affected infants significantly. …”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…8 PD is a pan-ethnic disease with an estimated frequency of 1:40,000, although recent reports from newborn screening studies suggest that PD may be more frequent. 1,8,10,11 The advent of recombinant human enzyme replacement therapy (ERT) has improved quality of life and reduced morbidity and mortality in the majority of patients with both infantile-onset PD 11,12 and later-onset PD. 13 Recombinant human GAA (rhGAA) is harvested from Chinese hamster ovary (CHO) cells and exerts its activity after proteolytic cleavage in the lysosomes.…”
mentioning
confidence: 99%
“…However, these studies demonstrated an efficient glycogen clearance in cardiac muscle and liver while a modest effect was observed in skeletal muscle (17,18). Clinical studies based on the administration of rhGAA in classical infantile Pompe patients showed a prominent effect on cardiac hypertrophy, motor skill improvement as well as substantial life-span increase (19)(20)(21)(22). Administration of recombinant enzyme in late-onset patients results in a mild improvement of motor and respiratory functions, but ERT efficacy in these patients needs to be evaluated at long-term (23,24).…”
Section: Ert In Mice and Humanmentioning
confidence: 99%